Pengenalan Dasar Pemrograman Python Dengan Google Colaboratory - Febby Wilyani; Qonaah Nuryan Arif; Fitri Aslimar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This activity aims to explore the use of Google Colaboratory as a basic introduction tool to Python programming. The research methodology involves analyzing the features of Google Colaboratory, implementing basic Python code, and observing user experiences. Research findings indicate that Google Colaboratory provides high accessibility without the need for additional installation or configuration requirements, enabling users to quickly initiate Python programming. Furthermore, the platform offers sharing and online collaboration capabilities and provides computational resources suitable for intensive data processing tasks. The implications of this research suggest that Google Colaboratory can be an effective solution in supporting Python programming learning, especially for beginners. With a user-friendly interface and easy access, this platform has the potential to facilitate the development of programming skills for a broader audience.